2021
DOI: 10.1016/j.mehy.2021.110641
|View full text |Cite
|
Sign up to set email alerts
|

Highly expressed ACE-2 receptors during pregnancy: A protective factor for SARS-COV-2 infection?

Abstract: While previous viral pandemics showed that pregnancy was a risk factor for susceptibility and adverse outcomes, current evidence is conflicting whether SARS-CoV-2 infection during pregnancy is more severe than in the general population, with relatively low maternal and fetal/neonatal mortality rates. SARS-CoV-2 is known to enter host cells via the ACE-2 receptors, competitively occupying their binding sites. In theory, viral invasion can lead to a reduction in available ACE-2 receptors and consequently an unba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
0
8
0
1
Order By: Relevance
“…Such an imbalance might amplify pathological vasoconstriction, brosis, in ammation, and thrombosis, all of which are detrimental to the pregnancy process. [25] The infection may also interfere with the normal functioning of endometrial cells, contributing to reproductive failure such as miscarriage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such an imbalance might amplify pathological vasoconstriction, brosis, in ammation, and thrombosis, all of which are detrimental to the pregnancy process. [25] The infection may also interfere with the normal functioning of endometrial cells, contributing to reproductive failure such as miscarriage.…”
Section: Discussionmentioning
confidence: 99%
“…This is partly due to the differing levels of binding a nity that ACE2 receptors have for the S-protein of the virus. [25] Additionally, earlier research has indicated that in ammasomes play a role in the pathophysiology of the infection, suggesting that they could serve as indicators of COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%
“…ACE2 is located weakly only at the stromal side of the syncytiotrophoblast of the trophoblast villous, whereas it is quite indetectable on the maternal endothelial side that hosts few TMPRSS2 receptors [ 10 ], partially explaining the extremely rare vertical transmission [ 16 , 23 ]. The main biological role of ACE is to convert angiotensin I (Ang I) to angiotensin II (Ang II), which binds AT1 receptors [ 24 ]. At the same time, ACE2 produces angiotensin 1-7 (Ang 1-7) that inhibits AT II via the activation of the anti-inflammatory MAS receptors [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main biological role of ACE is to convert angiotensin I (Ang I) to angiotensin II (Ang II), which binds AT1 receptors [ 24 ]. At the same time, ACE2 produces angiotensin 1-7 (Ang 1-7) that inhibits AT II via the activation of the anti-inflammatory MAS receptors [ 24 ]. Ang 1-7 determines vasodilating, anti-inflammatory, anti-fibrotic, and anti-thrombotic effects [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Um fator primordial na evolução da doença é o estado de imunidade, tendo os indivíduos com imunidade mais comprometida uma maior chance de doença severa, com maior possibilidade de agravamento e necessidade de suporte intensivo. Esses são notadamente os idosos e as gestantes com comorbidades como hipertensão, diabetes e obesidade (Figueiro-Filho, 2021;Wang et al, 2022).…”
Section: Introductionunclassified